Penyuluhan Kesehatan Penggunaan Masker pada Masyarakat Dusun Kampung Parang Desa Bontoramba Kec. Bontonompo Selatan Kab. Gowa Sulawesi Selatan - Mikawati Mikawati; Makkasau Makkasau; Kens Napolion; Muhammad Thabran Talib; Nofianti Nofianti (PT.Mantaya Idea Batara, 2022)
This community partnership program (PKM) is carried out on the villagers of Parang village of Bontoramba Village of South Bontonompo Subdistrict by involving Bontonompo Health Center as the person in charge of the work area that has the target of activities. In general, the purpose of this PKM progran is increased knowledge can affect attitudes followed by behavioral changes in this case is to use masks when doing activities outside the home. A special target is all villagers of Parang village, through this activity is for villagers to know the correct use of masks. The method used in achieving the goal is counseling with the question and answer lecture method (CTJ) to the target and villagers of Parang village of Bontoramba Village of South Bontonompo Subdistrict. The results of PKM activities are expected to be in accordance with the objectives and targets of the active role of participants during the activity.